EKSPLORASI BUDAYA MAKAN MERAWANG SEBRANG KOTA JAMBI DALAM SENI PERTUNJUKAN TARI TRADISIONAL - Farazwati, Adinda; Syahirah, Dhiyan; Yanti, Alta Dama; Efriyani, Sari; Rahayu, Ajeng; Pratiwi, Destri Aulia; Ningsih, Sulistia; Putri, Aulya Herliyana; Ramadona, Bunga Okta; Handayani, Nonia; Manurung, Widia Lestari; Sinurat, Ester; Dongoran, Anita; Suari, Silvia Dian; Yopi; Agneska, Widya; Paturrahman, Aprian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT Indonesia has a very rich cultural diversity, one of which is the tradition of eating merawang which comes from Seberang Jambi City. This tradition is not just about eating together, but also reflects social values such as togetherness, mutual cooperation, and simplicity in the life of the Jambi Malay community. Along with the times, the culture of eating merawang began to be explored in the performing arts, especially traditional dance, to preserve local culture and as a means of education for the younger generation. This study uses a qualitative descriptive method with data collection techniques through literature study and direct observation. The results of the study show that the culture of eating merawang is represented in dance through various aspects, such as dance movements that depict eating together, costumes and props that reflect the identity of Jambi Malay culture, as well as stage arrangements and accompanying music that create a traditional atmosphere. The narrative in the show also clarifies the social meaning contained in this culture. The exploration of the culture of eating merawang in dance not only serves to preserve culture, but also as a means of promotion that introduces local culture to the national and international levels. The incorporation of cultural elements in performing arts provides space for artists to innovate without ignoring existing cultural roots. Thus, this exploration is a real step to maintain the traditions and social values contained in the culture of eating merawang.